Adipose tissue metabolism and obesity - Lafontan, Max (Henry Stewart Talks, 2009)
Experimental approaches for study of adipose tissue biology, Lipoprotein lipase and triacylglycerol hydrolysis, Fatty acid uptake by fat cells, Triacylglycerol synthesis, Lipid droplets, Adipocyte lipases, Lipid droplet proteins, Catecholamine-induced lipolysis, Catecholamine and insulin signalling pathways, Natriuretic peptides, Atrial natriuretic peptide and lipolysis, Lipid mobilization in lean and obese patients, In situ microdialysis and lipolysis exploration, Exercise-induced lipid mobilization in lean and obese, Role of catecholamines, Alpha2-adrenergic responsiveness and obesity, Natriuretic peptides and lipid mobilization